The Child and the Blade: An Archetypal Analysis of Mongolian and Cross-Cultural Hair-Cutting Rituals (Asian Journal of Social Science Studies, 2025)
Rituals play a significant role in shaping individual life cycles, social relationships, and worldviews, particularly those related to childbearing, blessings, and protection. These rituals not only reflect the customs of families, communities, and ethnicities but also serve as key factors in societal formation. Carl Jung's concept of archetypes as "deep, repetitive, meaningful actions within the human ritual system" forms a core framework for understanding these practices across various fields such as anthropology, psychology, and cultural studies. This study examines Mongolian child-related rituals, focusing on the "Daakhi Ürgeekh" (first hair-cutting ceremony) ritual, through the lens of archetypal pattern. The research draws upon diverse theoretical perspectives, including the works of Jung, Turner, Campbell, and Lévi-Strauss, to explore the symbolic, mythological, and psychological structures underlying these rituals. Utilizing ethnographic observation, oral tradition collection, and comparative analysis, this study reveals shared archetypes and culturally specific adaptations across Mongolian, Greek, Hindu, and Jewish traditions. By analyzing these rituals as rites of passage, this study provides deeper insight into the protective, blessing, and transitional aspects of Mongolian customs and contributes to the broader understanding of ritual and archetypal symbolism in human culture.